The Effect of Digitization of Public Services and Organizational Culture on the Competence of State Civil Servants Towards Integrated Government - Anwar Sadat (Journal of Social Science, 2025)
Digitalization of public services is a strategic step to improve efficiency, transparency, and accountability in government. On the other hand, a strong organizational culture can create a work environment that supports the improvement of the competence of the State Civil Apparatus (ASN). This study aims to analyze the relationship between the digitalization of public services, organizational culture, and ASN competence in Baubau City, as well as variables that drive digital transformation. A quantitative approach based on the philosophy of positivism was used in this study. The results showed that the Public Service Digitalization variable had a positive and significant effect on ASN competence, by having a positive and significant C.R (Critical Ratio) value. While the organizational culture variable has a positive and insignificant effect on ASN Competence. Integrated Government has a positive and insignificant effect on ASN Competence. The Integrated Government variable can mediate the influence between Digitalization of Public Services and Organizational culture on ASN Competence. The results of this study are expected to be used as an alternative decision-making for the Regional Government in designing public service innovations that are utilized by the community, increasing ASN awareness of the importance of organizational culture, and providing training to support the optimal implementation of public service digitization. The implementation of this strategy is expected to improve the quality of public services and provide tangible benefits to the community.